Penggunaan Obat Herbal pada Pasien Kanker Serviks - MAKSUM RADJI; HENDRI ALDRAT; YAHDIANA HARAHAP; COSPHIADI IRAWAN (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
Herbal medicines have widely been used to treat many type of diseases despite the advance of standard or conventional therapy. In fact, many people in Indonesia use medicinal plant as their customary part of life. Therefore, it is necessary to further explore the use of herbal medicines through modern perception. ln this study we would like to know the frequency and species of herbal medicines used among cervical cancer patients in National Cancer Hospital Dharmais, Jakarta, Indonesia and also to assess the relationship between age, education, jobs, stage of cancer, and payment status of the patients. The results were 61,8% patients used herbal medicines. The herbal medicines used most were mahkota dewa (Phaleria macrocarpa Scheetf Boerl.) 35.3%, temu putih (Curcuma zedoaria Rosc.) 32.4%, and buah merah (Pandanus conoideus Lam) 17,6%. There was a significant relationship (p=0,039) between the use of herbal medicines and stage of cancer but no relationship between age, education, occupation, income and payment status with the use of herbal medicines.